Wawasan Ekologi Dalam Al-Quran (Kajian Tematis Ayat-Ayat Biah) - Hidayah, Sani Asrofil; Hilyati Aulia (Aqwal: Journal of Qur'an and Hadis Studies, 2022)
Quran as a human guide book should not only discuss about divine themes, but also as a source of reference related to practical problems such as environment, especially how humans can know and understand well their environment in which they live until the concept of ideal biah can be realized. This paper will introduce elogical insight which its pattern can be read in some verses of Quran. This paper focuses on biah’s verses. The method that will be used in this paper is thematic interpretation method, in which biah’s verses are the main study, which will be analyzed from a historical perspective, therefore the moral idea behind the verses is taken and the values obtained are universal and relevant. This ecological insight is used as the basic for realizing the ideal biah for all human beings.